(untitled) (Avaliação: Revista da Avaliação da Educação Superior, 2021)
Among the quality indicators released by the Brazilian Higher Education Assessment System (Sinaes), the Indicator “Difference between Observed and Expected Performance” (IDD) has the purpose of measuring the contribution of the course to student achievement during undergraduate programs. The research presented here offers a new methodology for calculating the IDD (Model IDD-VDCF), examining the philosophical and statistical underpinnings of quality measures, focusing on those that capture the value-added as a student achievement growth. The survey included a sample of 30,668 students, from 911 accounting undergraduate programs in Brazil. The insertion of control variables (at the student and at the institution level) reduced the bias of the IDD estimate associated with the student’s selection in specific Accounting Sciences courses. The results call attention to the need to consider the students’ learning context when one wants to compare the performance between institutions based on standardized tests. The major contribution of this work is the development of a measure that disentangles more fully what the contribution of program is to student learning, and what merely is a reflection of the capacity that a student brought to the program.